Peningkatan Hasil Belajar Siswa dengan Menggunakan Model Kooperatif Tipe Numbered Heads Together di Sekolah Dasar - Lisa Nasevalna; Mayarnimar Mayarnimar (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2019)
The purpose of this research was to describe the improvement of integrated thematic learning outcomes using the Numbered Heads Together (NHT) type cooperative model at 4th grade of elementry school in Pahambatan of Balingka. The research subjects were teachers and 20 students.  Research site in Pahambatan of Balingka. The result showed an increase in : a)RPP cycle I 83,33% (good) and cycle II 94,44% (very good) b)implementation in the aspects of teacher cycle I 81,24% (good) and cycle II 93,75% (very good) whilw implementation of aspectcts of students cycle I 81,24% (good) and cycle II 90,62% c) aseesment of the result of student alignment with the average in cycle I 71,47 and cycle II with an average of 81,24. Based on these results it can be concluded that the numbered heads together (NHT) of cooperative model can improve integrated thematic learning outcomes in students.Keyword: numbered heads together model,learning outcomes